Morphological on the Macroscropic Development of the Stomach in the Long-tailed Macaque (Macaca fascicularis) during Pre Natal and Post Natal Period - Erdiansyah Rahmi (Universitas Syiah Kuala, 2007)
This research was conducted with aim to reveal the morphological changes on the stomach in thelong-tailed macaque (Macaca fascicularis) (Mf) during prenatal and postnatal development. Stomachtaken from seven fetuses (40, 55, 70, 85, 100, 120, and 150 gestation day) and two newborns (10 and 105day old) animals was used in this study. The stomach was studied at macroscopic for observation of thegeneral structure. Measurement conducted to stomach length, wide of stomach body, greater curvature,lesser curvature of the stomach in each of old age group. Perception result indicate that the stomach of Mf was red bean like in form with short minor kurvatura. These values increased along with the age of fetusand infant. The Lesser curvature very short. Greater curvature relative length (twice improvement) atpost natal (infant) compared to before birth (fetus). The morphological development of the stomachincreased with age, with very rapid further development after birth, which is possibly due to the age of thefetus and in addition, the start of digestive activity and optimalization of stomach function.Keywords: anatomy, digestion, primates